Brain-derived extracellular vesicles: A promising avenue for Parkinson’s disease pathogenesis, diagnosis, and treatment - Shurui Zhang; Jingwen Li; Xinyu Hu; Hanshu Liu; Qinwei Yu; Guiying Kuang; Long Liu; Danfang Yu; Zhicheng Lin; Nian Xiong (Neural Regeneration Research, 2026)
The misfolding, aggregation, and deposition of alpha-synuclein into Lewy bodies are pivotal events that trigger pathological changes in Parkinson’s disease. Extracellular vesicles are nanosized lipid-bilayer vesicles secreted by cells that play a crucial role in intercellular communication due to their diverse cargo. Among these, brain-derived extracellular vesicles, which are secreted by various brain cells such as neurons, glial cells, and Schwann cells, have garnered increasing attention. They serve as a promising tool for elucidating Parkinson’s disease pathogenesis and for advancing diagnostic and therapeutic strategies. This review highlights the recent advancements in our understanding of brain-derived extracellular vesicles released into the blood and their role in the pathogenesis of Parkinson’s disease, with specific emphasis on their involvement in the aggregation and spread of alpha-synuclein. Brain-derived extracellular vesicles contribute to disease progression through multiple mechanisms, including autophagy-lysosome dysfunction, neuroinflammation, and oxidative stress, collectively driving neurodegeneration in Parkinson’s disease. Their application in Parkinson’s disease diagnosis is a primary focus of this review. Recent studies have demonstrated that brain-derived extracellular vesicles can be isolated from peripheral blood samples, as they carry α-synuclein and other key biomarkers such as DJ-1 and various microRNAs. These findings highlight the potential of brain-derived extracellular vesicles, not only for the early diagnosis of Parkinson’s disease but also for disease progression monitoring and differential diagnosis. Additionally, an overview of explorations into the potential therapeutic applications of brain-derived extracellular vesicles for Parkinson’s disease is provided. Therapeutic strategies targeting brain-derived extracellular vesicles involve modulating the release and uptake of pathological alpha-synuclein -containing brain-derived extracellular vesicles to inhibit the spread of the protein. Moreover, brain-derived extracellular vesicles show immense promise as therapeutic delivery vehicles capable of transporting drugs into the central nervous system. Importantly, brain-derived extracellular vesicles also play a crucial role in neural regeneration by promoting neuronal protection, supporting axonal regeneration, and facilitating myelin repair, further enhancing their therapeutic potential in Parkinson’s disease and other neurological disorders. Further clarification is needed of the methods for identifying and extracting brain-derived extracellular vesicles, and large-scale cohort studies are necessary to validate the accuracy and specificity of these biomarkers. Future research should focus on systematically elucidating the unique mechanistic roles of brain-derived extracellular vesicles, as well as their distinct advantages in the clinical translation of methods for early detection and therapeutic development.